(untitled) (Journal of Engineering, 2023)
Lead-acid batteries have been used increasingly in recent years in solar power systems, especially in homes and small businesses, due to their cheapness and advanced development in manufacturing them. However, these batteries have low voltages and low capacities, to increase voltage and capacities, they need to be connected in series and parallel. Whether they are connected in series or parallel, their voltages and capacities must be equal otherwise the quality of service will be degraded. The fact that these different voltages are inherent in their manufacturing, but these unbalanced voltages can be controlled. Using a switched capacitor is a method that was used in many methods for balancing voltages, but their responses are slow. To increase the response and control of the balancing process, this research proposes a novel technique that consists of a dynamic capacitor for controlling the unbalanced voltages of series-connected lead-acid batteries. The proposed technique uses a main capacitor and an inductor with two switches their on/off states are controlled through a pulse width modulation. The technique is designed and validated using MATLAB/Simulink and the results for different cases are compared with other techniques such as switched capacitor technique. Results show that the proposed method promised the balancing control in a shorter time and better performance than other techniques which are crucial in the battery’s voltage balancing.